The Herbal Drug Melampyrum pratense L. (Koch): Isolation and Identification of Its Bioactive Compounds Targeting Mediators of Inflammation - Vogl, S. (Hindawi Publishing Corporation, 2013)
Melampyrum pratense L. (Koch) is used in traditional Austrian medicine for the treatment of different inflammation-related conditions. In this work, we show that the extracts of M. pratense stimulated peroxisome proliferator-activated receptors- (PPARs-)α and -γ that are well recognized for their anti-inflammatory activities. Furthermore, the extract inhibited the activation of the proinflammatory transcription factor NF-κB and induction of its target genes interleukin-8 (IL-8) and E-selectin in vitro. Bioassay-guided fractionation identified several active flavonoids and iridoids including melampyroside and mussaenoside and the phenolic compound lunularin that were identified in this species for the first time. The flavonoids apigenin and luteolin were distinguished as the main components accountable for the anti-inflammatory properties. Apigenin and luteolin effectively inhibited tumor necrosis factor α (TNF-α)-induced NF-κB-mediated transactivation of a luciferase reporter gene. Furthermore, the two compounds dose-dependently reduced IL-8 and E-selectin protein expression after stimulation with lipopolysaccharide (LPS) or TNF-α in endothelial cells (ECs). The iridoids melampyroside and mussaenoside prevented the elevation of E-selectin in LPS-stimulated ECs. Lunularin was found to reduce the protein levels of the proinflammatory mediators E-selectin and IL-8 in ECs in response to LPS. These data validate the ethnomedical use of M. pratense for the treatment of inflammatory conditions and point to the constituents accountable for its anti-inflammatory activity.